Synthesis of New Oxindoles and Determination of Their Antibacterial Properties - Pablo E. Romo; Braulio Insuasty; Rodrigo Abonia; María del Pilar Crespo; Jairo Quiroga (Heteroatom Chemistry)
A versatile method for the synthesis of new oxindoles was developed by the reaction between substituted isatins and 5-aminopyrazoles. The reaction was carried out at room temperature in ethanol using p-toluenesulfonic acid as the catalyst. The products were obtained with acceptable to excellent yields (44–96%). Structures of the new compounds were unambiguously established by spectroscopic and analytical techniques. The antibacterial activity was determined by microdilution assays. Compounds 3b, 3e, and 3g showed antistaphylococcal activity, particularly compound 3e displayed a potent activity against the vancomycin intermediate Staphylococcus aureus (VISA). Compounds 3i, 3j, and 3o inhibited Neisseria gonorrhoeae growth.